1979
DOI: 10.1071/bi9790423
|View full text |Cite
|
Sign up to set email alerts
|

Microfibrillar Proteins of Wool: Partial Specific Volumes and Molecular Weights in Denaturing Solvents

Abstract: Aust. J. Bioi. Sci., 1979. 32, 423-35 The molecular weights of the reduced and S-carboxymethylated microfibrillar protein components of wool have been investigated by sedimentation equilibrium in 6 M guanidine hydrochloride and by sodium dodecyl sulfate-polyacrylamide gel electrophoresis. The microfibrillar proteins have molecular weights of 57000 (component 5), 58000 (component 7c); 50000 (component 8c-l) with a range of values for the other component 8 polypeptide chains of 45 000--50 000. The proteins mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
1

Year Published

1981
1981
1997
1997

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 28 publications
4
10
1
Order By: Relevance
“…While our M, estimations are in fair agreement with those reported for S-carboxy-methylated type I1 a-keratins of sheep wool (e.g. [12,87), they are considerably lower than those (M, 67,000 -76,000) previously given for the corresponding human hair a-keratins [4, 551. The relatively basic character of these polypeptides could not be recognized in previous analyses of hair akeratins from sheep wool, human scalp and other sources, because the S-carboxymethylation employed converted them to much-more-negatively charged polypeptides [ 12, 34, 55, 561. As the subdivision of a-keratins into type I and I1 polypeptides was originally made for sheep wool keratins [10--14, 37, 431, a comparison of our data from proteins of living trichocytes with the sheep wool a-keratin data in the literature is particularly interesting.…”
Section: -supporting
confidence: 90%
“…While our M, estimations are in fair agreement with those reported for S-carboxy-methylated type I1 a-keratins of sheep wool (e.g. [12,87), they are considerably lower than those (M, 67,000 -76,000) previously given for the corresponding human hair a-keratins [4, 551. The relatively basic character of these polypeptides could not be recognized in previous analyses of hair akeratins from sheep wool, human scalp and other sources, because the S-carboxymethylation employed converted them to much-more-negatively charged polypeptides [ 12, 34, 55, 561. As the subdivision of a-keratins into type I and I1 polypeptides was originally made for sheep wool keratins [10--14, 37, 431, a comparison of our data from proteins of living trichocytes with the sheep wool a-keratin data in the literature is particularly interesting.…”
Section: -supporting
confidence: 90%
“…Amino acid sequencing has recently indicated that component 5 belongs to the component 7 family (L. Sparrow, personal communication, 1984). It can be noted that the monomeric molecular weight values determined by ultracentrifugation have been recently refined (Woods 1979). Furthermore, molecular weights (Mr) of all SCM-kerateine proteins determined by SDS-polyacrylamide gel electrophoresis are subject to error and this error increases with increased SCM-cysteine content of the pro teins (Woods 1979;Marsha1l1983).…”
Section: Low-sulphur Pro Teins (Microfibril or Intermediate Filament mentioning
confidence: 98%
“…The densities were measured at 20 ± O· 02°C with a precision density-meter DMA-02C (Anton Parr, Graz) and protein concentrations were determined from the dry weights of the solution and its diffusate as described by Woods (1979). The absorbance and specific refractive index increment were determined on the same solutions as used for the partial specific volume measurements and are given in Table 1.…”
Section: Physical Methodsmentioning
confidence: 99%
“…Molecular weights were measured by the low-speed equilibrium method (Richards et al 1968) and by the meniscus-depletion method of Yphantis (1964). A six-channel centre piece was employed for the conventional equilibrium runs with column heights of 2 mm and the methods used to evaluate the molecular weights have been given in a previous paper (Woods 1979). For the meniscus-depletion experiments regular double-sector cells were used with column heights of 3 mm.…”
Section: Physical Methodsmentioning
confidence: 99%
See 1 more Smart Citation